Chronicle of incompetence. - Fletcher, Martin (New Statesman, 2020)
Downing Street insisted afterwards that Britain was "well prepared" and Chris Whitty, the government's chief medical adviser for England, praised the country's "strong track record of managing new forms of infectious diseases". Shortly after he succeeded May last July, Johnson abolished the government's anti-pandemic committee - the threats, hazards, resilience and contingency committee - as part of his plan to streamline Whitehall, according to the Daily Mail. At the height of the crisis the government was left essentially leaderless for two or three weeks when Johnson was struck down by Covid-19. 18 JUNE The government scraps its contact-tracing app, admitting it is flawed, despite Boris Johnson's previous boasts that it would be "world-beating".